Development of Lewis pair methodologies for advanced polymer synthesis and application - McGraw, Michael Lawrence, author; Chen, Eugene Y.-X., advisor; Bailey, Travis S., committee member; Rappe, Anthony K., committee member; Linden, James C., committee member (Colorado State University. Libraries, 2022)
This dissertation describes the development of new chemistries related to Lewis pair polymerization methodology with emphasis on chemical selectivity and control. Selectivity is defined as the ability to promote desirable chemistry while simultaneously discouraging unwanted chemistry. Control is defined as the ability to target specific and highly sophisticated products from the outset and the ability to reliably achieve that desired product as a consequence of predictable reaction behavior. The themes contained herein relate to catalysis, mechanism elucidation and application, polymer synthesis, and green chemistry. Chapter 1 introduces LPP and includes sections from my published perspective article Lewis Pair Polymerization: Perspective on a Ten-Year Journey. This chapter includes a brief history of the technique, as well as mechanistic fundamentals and key features of the method. Chapters 2 & 3 describes the LPP of the challenging biorenewable monomer methyl crotonate. Chapter 4 describes the invention of the compounded sequence control (CSC) LPP method. Chapter 5 discusses the application of CSC to the synthesis of more advanced cyclic diblock structures using by utilizing a unique sorbate-based initiation system. Chapter 6 details the mechanism by which the sorbate-based initiation system effects cyclization to produce cyclic polymers with spatial and temporal control. Finally, Chapter 7 offers some conclusions and future directions.
Keywords: controlled polymerization; acrylates; Lewis pair